Rancang Bangun Sistem Cerdas Pengatur Kelembaban Tanah Pada Greenhouse untuk Tanaman Mawar menggunakan Esp32 - Gaspar, Abril; Arifin, samsu (JURNAL SISTEM KOMPUTER ASIA, 2023)
The agricultural sector is one of the important economic sectors in Indonesia. One of the well-known agricultural sub-sectors is roses. Roses are commonly used as cut flowers with the aim of being used in various fields such as decoration, culture, worship and also as processed products so that roses with good quality are needed. However, cultivating roses is not as easy as other flowers. Roses require extra attention in various fields, one of which is the quality of soil moisture. It takes more energy and time to check and also regulate soil moisture so that it meets the needs of roses. However, until now checking and also regulating soil moisture is still done manually so it is less efficient, this is due to the lack of application of technology. Based on the problems above, to increase the efficiency of time and energy, it is necessary to apply the right technology, one of the technologies applied is the ESP32 microcontroller and soild moisture sensor. The ESP 32 microcontroller is a small computer that has a specific operating system, ESP32 also has many excellent features such as Analog and Digital input/output, PWM, SPI, I2C, etc. ESP32 is very suitable for processing / operating various sensors, one of the sensors to be used is soil moisture. Soil moisture sensor is a sensor that functions to detect soil moisture values. Soil moisture sensors and ESP32 will be used to design a plant watering tool that can work automatically by processing data from soil moisture. Soil moisture data will be processed by ESP32, the processed results will determine the value of the current soil moisture condition and will water automatically if the soil moisture condition is less than the required standard.